Residual activity in a Nuclear Medicine Department: a dosimetric study - Queirós, André (2022)
The exposure to ionizing radiation by radiographer in Nuclear Medicine (NM) Departments is inevitable, as this area has the highest rates of residual activity. Since 1957, and later updated (2005), several guidelines have been established by the IAEA (International Atomic Energy Agency), for the management of residues from radioactive use for medical purposes, with the intention of increasing the radiological protection of the people and the environment. Optimized management is very important not only for the functioning of the NM department, but also for the...